Purification and properties of glutathione transferase from Issatchenkia orientalis. - Tamaki, H (1989)
Glutathione transferase (GST) (EC 2.5.1.18) was purified from a cell extract of Issatchenkia orientalis, and two GST isoenzymes were isolated. They had molecular weights of 37,500 and 40,000 and were designated GST Y-1 and GST Y-2, respectively. GST Y-1 and GST Y-2 gave single bands with molecular weights of 22,000 and 23,500, respectively, on sodium dodecyl sulfate-polyacrylamide gel electrophoresis. GST Y-1 and GST Y-2 were immunologically distinguished from each other. GST Y-1 showed specific activity 10.4-times and 6.0-times higher when 1-chloro-2,4-dinitrobenzene and o-dinitrobenzene were used as substrates, respectively, than GST Y-2. GST activity was not detected for either isoenzyme when other substrates such as bromosulfophthalein and trans-4-phenyl-3-buten-2-one were used. GST Y-1 and GST Y-2 had Km values of 0.51 and 0.75 mM for glutathione, respectively, and of 0.16 and 4.01 mM for 1-chloro-2,4-dinitrobenzene. GST Y-1 was significantly inhibited by Cibacron blue 3G-A, and GST Y-2 was significantly inhibited by bromosulfophthalein.